Electronic device use and depressive symptoms in college students mediated by sleep onset time - Lele Xiao; Su Xiao; Jie Wang; Yongshuo Zhang; Chong Zhang; Yuqing Yan (Scientific Reports)
Abstract This study aimed to examine the association between electronic device use duration and depressive symptoms among Chinese college students, while also exploring the mediating role of sleep onset time. Data were collected from university students in Xuzhou City, Jiangsu Province, China. Statistical analyses were conducted using STATA 17.0. Ordinary least squares (OLS) regression was employed for both univariate and multivariate analyses. Additionally, a stepwise regression approach was used to assess the mediating effect of sleep onset time. A total of 1,160 valid cases were included in the final analysis. The regression results indicated a significant positive association between electronic device use duration and depressive symptoms, even after adjusting for all control variables. Furthermore, stepwise regression analysis confirmed that sleep onset time partially mediated the relationship between electronic device use and depressive symptoms. Sleep onset time serves as a mediating factor in the link between electronic device use and depressive symptoms. Interventions aimed at promoting healthier lifestyle habits, such as reducing screen time and encouraging physical activity, may help improve the mental well-being of college students.